Detectable Impact of Local and Remote Anthropogenic Aerosols on the 20th Century Changes of West African and South Asian Monsoon Precipitation. Issue 10 (17th May 2018) - Undorf, S.; Polson, D.; Bollasina, M. A.; Ming, Y.; Schurer, A.; Hegerl, G. C.
Abstract: Anthropogenic aerosols are a key driver of changes in summer monsoon precipitation in the Northern Hemisphere during the 20th century. Here we apply detection and attribution methods to investigate causes of change in the West African and South Asian monsoons separately and identify the aerosol source regions that are most important for explaining the observed changes during 1920–2005. Historical simulations with the GFDL‐CM3 model are used to derive fingerprints of aerosol forcing from different regions. For West Africa, remote aerosol emissions from North America and Europe (NAEU) are essential in order to detect the anthropogenic signal in observed monsoon precipitation changes. The changes are significantly underestimated in the model, however. While natural (volcanic) forcing seems to also play a role, the dominant contribution is found to come from aerosol‐induced changes in the interhemispheric temperature gradient and associated meridional shifts of the Intertropical Convergence Zone. For South Asia, in contrast, changes in observed monsoon precipitation cannot be explained without local emissions. Here the findings show a weakening of the monsoon circulation, driven by the increase of remote NAEU aerosol emissions until 1975, and since then by the increase in local emissions offsetting the decrease of NAEU emissions. The results show that the aerosol forcing from individual emission regions is strong enough to be detected over internal variability. They also underscore the importance of the spatial pattern of global‐aerosol emissions, which is likely to continue to change throughout the expected near‐future decline in global emissions. Key Points: Impact of anthropogenic aerosols by source region is detected on 20th century West African and South Asian monsoon precipitation changes South Asian/West African monsoon precipitation changes are dominated by aerosols from South Asia/North America and Europe Changes in West Africa are related to a shift in circulation; those in South Asia are associated with a weakening of the monsoon circulation